Contribution of area-based fisheries management measures to fisheries sustainability and marine conservation: a global scoping review - Dimitra Petza; Panagiotis Anastopoulos; Stefanos Kalogirou; Marta Coll; Serge Garcia; Michel Kaiser; Nikoletta Koukourouvli; Irene Lourdi; Jake Rice; Marija Sciberras; Stelios Katsanevakis (Reviews in Fish Biology and Fisheries, 2023)
Area-based fisheries management measures (ABFMs) are commonly related to the sustainable use of resources but are increasingly considered broader conservation measures. This Scoping Review (ScR) identified and mapped the evidence base regarding the contribution of ABFMs to fisheries sustainability and marine conservation. The ScR was conducted following the JBI methodology and the PRISMA statement. A total of 2,391 documents were identified, and following a two-stage screening process, 151 documents were eventually included in the ScR for full review and data extraction. Most of the documents were published during the last 12 years. Studies had a wide geographical distribution (mainly located in Europe and North America), were primarily conducted at the subnational level, concerned fishing restrictions of towed gears, and assessed ABFMs from a single stock’s perspective. ABFMs identified were of various types, and the use of terminology was not consistent in the literature. Multiple combinations of data collection (primarily experimental surveys/sampling and open data sources) and analysis methods (most commonly, fisheries and ecological analyses and modelling) were applied (often in combination), using a variety of different metrics. Various knowledge gaps emerged, mainly related to the study of ABFMs networks and the application of an interdisciplinary and ecosystem-based approach for assessing ABFMs. The social, economic, and environmental impact of ABFMs was positive in most cases (56%) and in less cases negative (22%) or mixed (14%). This ScR is a valuable source of information for the contribution of ABFMs to rebuilding marine ecosystems and attaining CBD conservation targets through the lens of the OECM concept. Graphical abstract